The Effects Of Collaborative Knowledge Building And Analytics-Supported Reflective Assessment On Learners’ Interaction, Collaboration, Conceptual Understanding And Learning Approach - Ghazal, Samar Mohammed Abdullah (2024)
Premised on socio-constructivism, knowledge building and assessment theories, this study attempts to: (1) design a knowledge building environment, informed by knowledge building principles and analytics-supported reflective assessments, and evaluates its effects on learners’ conceptual understanding, approaches to learning, and conceptions of collaboration; (2) investigate the patterns of interaction in Knowledge Forum; (3) examine the role and process of reflective assessment in improving knowledge building; (4) characterize the dynamics of collaborative knowledge building, and (5) examine the role of interaction in Knowledge Forum (KF) on learners’ conceptual understanding. A mixed method (QUAN + QUAL) approach was adopted in this study involving 24 postgraduate students.